Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.081
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Labor in the Sharing Economy

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…Emotional labor has emerged as an important concept in looking at workers in an organizational context, while psychological research has shown its predictors and -often detrimental -outcomes. However, despite being a widely researched and striving field of research, scholars have only started to explore the prevalence, antecedents and outcomes of emotional labor in the sharing economy (Lutz et al, 2018). Existing studies on emotional labor in the sharing economy, reflecting a focus in the general literature, have focused on the provider side (Glöss et al, 2016;Raval and Dourish, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional labor has emerged as an important concept in looking at workers in an organizational context, while psychological research has shown its predictors and -often detrimental -outcomes. However, despite being a widely researched and striving field of research, scholars have only started to explore the prevalence, antecedents and outcomes of emotional labor in the sharing economy (Lutz et al, 2018). Existing studies on emotional labor in the sharing economy, reflecting a focus in the general literature, have focused on the provider side (Glöss et al, 2016;Raval and Dourish, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Academic literature has begun to engage with the notion that providers in the sharing economy are engaging in emotional labour (Glöss et al, 2016;Lutz et al, 2018;Newlands et al, 2017;Raval and Dourish, 2016;Rosenblat and Stark, 2016). Emerging from the seminal work of sociologist Arlie Russell Hochschild (1983), the concept of emotional labour concerns an individual's efforts to induce or suppress certain feelings so as to produce the outward expression of organizationally desired emotions.…”
Section: Social Dimensionmentioning
confidence: 99%
“…What is more, we argue that many of the challenges and issues that are present in digital online sharing are also highly relevant for the physical sharing in the context of the sharing economy, especially when shared physical objects (e.g., tools, apartments) have digital representations (e.g., a listing, classifieds) and/or are mediated by an online platform. Prior research on sharing economies demonstrated that the design of online platforms may have a profound effect on the endurance and growth of resource sharing communities [Lampinen et al, 2015;Mosconi et al, 2017], play an important role in establishing peers' interaction [Raval and Dourish, 2016], affect users' behavior [Lutz et al, 2018], and influence their decision-making [Edelman and Luca, 2014;Ert et al, 2016].…”
Section: Problem Statementmentioning
confidence: 99%
“…Prior work examined numerous issues that commercial sharing economy services face (e.g., transience among and anonymity of membership) [Bardhi and Eckhardt, 2012], outlined technical limitations (e.g., account sharing) of existing sharing economy platforms [Lampinen, 2014], discussed challenges related to disintermediation (e.g., out-of-platform transactions) [Bellotti et al, 2017], and argued for a significant role of emotional labor (i.e. the management of feelings) in the experience sharing services [Lutz et al, 2018].…”
Section: Studies Of Physical Sharing Practices In the Sharing Economymentioning
confidence: 99%
“…This concept is about the alteration of behaviors during an interaction, based on perceived information about a situation, and enables the individual to tailor the message to fit another individual's needs and preferences (see Franke & Park, ). Lutz, Newlands, and Fieseler () refer to this behavior as emotional labor. They found that in a sharing economy, the coercive nature of feedback mechanisms conditions both providers and consumers to illustrate emotional labor during service encounters.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%